2018
DOI: 10.3389/fphar.2018.01220
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of DOAC Prescribing Before and During Hospital Admission and Analysis of Determinants for Inappropriate Prescribing

Abstract: Background and Objectives: Appropriate dosing of direct oral anticoagulants (DOACs) is required to avoid under- and overdosing that may precipitate strokes or thromboembolic events and bleedings, respectively. Our objective was to analyze the appropriateness of DOAC dosing according to the summaries of product characteristics (SmPC). Furthermore, determinants for inappropriate prescribing were investigated.Methodology: Retrospective cohort study of hospitalized patients aged ≥60 years with at least one DOAC in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
75
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(88 citation statements)
references
References 35 publications
12
75
0
1
Order By: Relevance
“…In a real-world registry in Spain, the rate of underdosing and overdosing of DOAC therapy was 17.5% (93/530) and 14.9% (79/ 530), respectively [16]. Other retrospective studies conducted abroad indicate that 5.4-17.4% patients are prescribed inappropriate reduced doses of DOACs (Additional file 1: Table S2) [17][18][19][20]. In our study, it was found that the rate of underdosing has been decreasing every year.…”
Section: Discussionmentioning
confidence: 99%
“…In a real-world registry in Spain, the rate of underdosing and overdosing of DOAC therapy was 17.5% (93/530) and 14.9% (79/ 530), respectively [16]. Other retrospective studies conducted abroad indicate that 5.4-17.4% patients are prescribed inappropriate reduced doses of DOACs (Additional file 1: Table S2) [17][18][19][20]. In our study, it was found that the rate of underdosing has been decreasing every year.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence suggests the proportion of patients prescribed according to guidelines is suboptimal . Up to 25% of patients who are hospitalized and up to one‐third of ambulatory patients receive an inappropriate dose of NOAC . It has been shown that only certain risk criteria justify dose reduction (eg, renal impairment) .…”
Section: Resultsmentioning
confidence: 99%
“…30 Up to 25% of patients who are hospitalized and up to one-third of ambulatory patients receive an inappropriate dose of NOAC. 31,32 It has been shown that only certain risk criteria justify dose reduction (eg, renal impairment). 33 Under dosing with no renal indication resulted in a nearly five-fold increased risk of stroke without significant difference in major bleeding.…”
Section: Adherence Of Health Care Professionals To Guidelinesmentioning
confidence: 99%
“…Rivaroxaban is approved with other DOACs such as apixaban and dabigatran in many countries in adult patients for thromboprophylaxis after elective hip or knee replacement surgery, prevention of stroke and systemic embolism with non-valvular atrial fibrillation (AF), for the treatment of Deep Vein Thrombosis (DVT) and Pulmonary Embolism (PE), and prevention of recurrent DVT and PE [5][6][7][8][9][10][11][12][13]. Prevention of stroke in AF was by far the most prevalent indication for prescribing a DOAC [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…When choosing any of the DOACs, the dosage should consider patientspecific factors including age, weight, renal function, serum creatinine, concomitant medications, and the cause for prescribing the drug [14]. If the patient was already started on a DOAC before hospital admission, it is many countries [3,6].…”
Section: Rivaroxaban and Age Ethnicities And Body Mass Index (Bmi)mentioning
confidence: 99%